2000
DOI: 10.1111/1469-8986.3740427
|View full text |Cite
|
Sign up to set email alerts
|

The effects of caffeine on visual selective attention to color: An ERP study

Abstract: Event-related potentials were recorded from 11 subjects after ingesting caffeine (250 mg) or placebo. Subjects were instructed to attend selectively to stimuli with a specified color (red or blue) in order to react to the occurrence of a target within the attended category. Reaction times revealed faster responses for the caffeine condition, whereas no differences in strategy were observed. Color attention effects were identified as frontal selection positivity, occipital selection negativity, and N2b, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
5
20
0
Order By: Relevance
“…Warburton et al 2001). However, this appears to be a general facilitatory effect that is absent in tests of spatial attention (Kenemans and Verbaten 1998;Ruijter et al 2000). Thus, caffeine is an unlikely cause of the effects reported here.…”
Section: Discussionmentioning
confidence: 54%
“…Warburton et al 2001). However, this appears to be a general facilitatory effect that is absent in tests of spatial attention (Kenemans and Verbaten 1998;Ruijter et al 2000). Thus, caffeine is an unlikely cause of the effects reported here.…”
Section: Discussionmentioning
confidence: 54%
“…Streufert et al [99] have shown that caffeine increases the speed of processing new stimuli, which was later confirmed [53]. Lorist and Snel [100] have also shown better target detection and response preparation by caffeine, whereas Ruijter et al [101] have demonstrated that the quantity of information processed is greater after caffeine. Recently, caffeine was shown to improve alerting and executive control function in a dose-response manner, peaking at 200 mg [102].…”
Section: S243mentioning
confidence: 91%
“…Kawamura et al found that P300 amplitude and area were significantly increased after 30 min of caffeine intake (Kawamura et al, 1996). Ruijter et al found an increase in P2 amplitude after caffeine intake and interpreted it as an arousal increasing effect (Ruijter et al, 2000). Our earlier work showed that caffeine led to a significant increase in P3 amplitude and decrease in reaction time, thereby indicating facilitation of information processing and acceleration of motor responses (Dixit et al, 2004).…”
Section: Introductionmentioning
confidence: 95%